Prevalence and factors associated with adverse early childhood experiences: a population-based study in Ceará, Brazil - Maria Iara Socorro Martins; Hermano Alexandre Lima Rocha; Álvaro Jorge Madeiro Leite; Sabrina Gabriele Maia Oliveira Rocha; David Augusto Batista Sá Araújo; Márcia Maria Tavares Machado; Jocileide Sales Campos; Edgar Gomes Marques Sampaio; Anamaria Cavalcante e Silva; Luciano Lima Correia (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To estimate the prevalence of adverse childhood experiences and identify associated factors. Methods: A population-based cross-sectional study comprised data from a sample of 3,200 households with 3,566 children under 6 years of age, representative of the state of Ceará, Brazil. A multistage sampling approach was used, with stratification among the state capital, Fortaleza, and the 28 countryside municipalities, in which 160 census tracts were randomly selected, each one with a cluster of 20 households. The outcome variable was structured based on adverse childhood experiences as suggested by the Center for Disease Control and Prevention, according to the number of situations to which the child was exposed: 0-2, 3-5, and 6-9. Ordinal logistic regression multivariate model was applied to assess associations. Results: Among the 3,566 children studied, 89.7% (95%CI 88.7-90.7) were exposed to at least one adverse experience, of which the most prevalent were neglect, and emotional/physical abuse. The main factors associated were maternal advanced age and smoking, paternal absence, low education level of the head of the family, food insecurity and lack of a social support network. Conclusion: The study found a high occurrence of adverse early childhood experiences, particularly among preschool children born to mothers of older age, solo, who smoke and in a situation of social and economic vulnerability, including food insecurity, who should be target of control and prevention measures.